Regeneration promotion and income generation through scientific forest management in community forestry: a case study from Rupandehi district, Nepal - Khanal, Y.; Adhikari, S. (Banko Janakari, 2018)
Community forestry is the most popular programme of forestry sector in Nepal. Previously community forest management was protection oriented and nowadays it has become production oriented due to implementation of scientific forest management plan. Recent forest policy promotes the application of scientific management of all productive forests and now it becomes a novel programme in forestry sector. This study highlights the outputs of the first year of implementation of scientific forest management plan in seven community forests (CF) of Rupandehi district, Nepal. Both bio-physical and socio-economic data were collected and analyzed. Regeneration survey was carried out before and after one year of regeneration felling. Similarly data related to income generation and employment opportunities were collected and analyzed. The results showed that 6.4 times increase in seedlings and 3.4 times increase in saplings after one year of regeneration felling operation. Similarly, the average production of timber and fuel wood was 1,086 cft and 4.5 chatta per ha. during regeneration felling in studied CFs. Average income from the intensive managed area of CF was found to be NRs. 884,059.8 and local employment generation of 910 man-days per ha. This indicates scientific forest management is one of the best options for improving forest condition through promoting regeneration of the forest for future generation and generating income and employment opportunities for the users. Banko Janakari A Journal of Forestry Information for Nepal Special Issue No. 4, 2018, Page : 45-53